Stem cells for lupus nephritis: a concise review of current knowledge. (October 2018) - Sattwika, P D; Mustafa, R; Paramaiswari, A; Herningtyas, E H
Lupus nephritis (LN), a common manifestation of systemic lupus erythematosus (SLE), accounts for significant morbidity and mortality in SLE patients. Since the available standard therapies and biologic agents for LN are yet to achieve the desired response and have considerable secondary effects, stem cell therapy has now emerged as a new approach. This therapy involves the transplantation of hematopoietic stem cells (HSCs) and mesenchymal stem cells (MSCs). Our current review will highlight the progress of stem cell therapy for LN, along with the challenges encountered and the future direction of this approach.